Drowning and Nonfatal Drowning in Children and Adolescents: A Subsequent Retrospective Data Analysis - Sebastian Berger; Manuela Siekmeyer; Stefanie Petzold-Quinque; Wieland Kiess; Andreas Merkenschlager (MDPI AG, 2024)
Fatal and nonfatal drowning are among the leading causes of death and lifelong severe neurological impairment among children and adolescents. This study aimed to complement research from Leipzig 1994-2008 to seek trends within risk factors, treatments, and outcomes throughout the last decade. We retrospectively investigated data of 47 inpatients aged 0-18 admitted to Leipzig University Department of Pediatrics who matched ICD-10 code T75.1 from 2008 to 2020 and compared them to a preceding study at the same institution. We also examined the prognostic value of parameters regarding the patients' outcomes. There were three median incidents per annum. The median age was 2.75 years; 76% of incidents happened in males. An accumulation was seen during the summer months and weekends. Most drowning incidents occurred in private ponds or pools (48.9%). Thirty-nine children were discharged without resulting morbidity, four showed neurological impairment, and three died. Risk factors concerning age, sex, and incident characteristics were confirmed. Special supervision needs still apply to 1-3-year-old male children or children with pre-existing health conditions around private pools and ponds. Hospitalization duration shortened, and morbidity and lethality decreased since the previous study. There was structural improvement in primary care and medical documentation. Parameters suggesting good outcomes include a submersion time < 5 min, GCS > 3 points, spontaneous movement upon admission, remaining pupillary light response, the absence of cardiovascular arrest, body temperature ≥ 32 °C, pH > 7, blood glucose < 15 mmol/L, lactate < 14 mmol/L, base excess ≥ −15 mmol/L, and the absence of ARDS. Clear legislation can contribute to improved private home water safety. Further studies should include a broad in- and outpatient spectrum and standardized incident documentation presupposing Utstein-style reporting. Regular reinvestigation of consistent geographical regions facilitates process evaluations of drowning epidemiology and therapy evolution.